Rapid nanobody-based imaging of mesothelin expressing malignancies compatible with blocking therapeutic antibodies - Benloucif, Abdennour; Meyer, Damien; Balasse, Laure; Goubard, Armelle; Danner, Lucile; Bouhlel, Ahlem; Castellano, Rémy; Guillet, Benjamin; Chames, Patrick; Kerfelec, Brigitte (Frontiers in Immunology, 2023)
Introduction Mesothelin (MSLN) is overexpressed in a wide variety of cancers with few therapeutic options and has recently emerged as an attractive target for cancer therapy, with a large number of approaches currently under preclinical and clinical investigation. In this respect, developing mesothelin specific tracers as molecular companion tools for predicting patient eligibility, monitoring then response to mesothelin-targeting therapies, and tracking the evolution of the disease or for real-time visualisation of tumours during surgery is of growing importance. Methods We generated by phage display a nanobody (Nb S1) and used enzymatic approaches were used to site-directed conjugate Nb S1 with either ATTO 647N fluorochrome or NODAGA chelator for fluorescence and positron emission tomography imaging (PET) respectively. Results We demonstrated that Nb S1 displays a high apparent affinity and specificity for human mesothelin and demonstrated that the binding, although located in the membrane distal domain of mesothelin, is not impeded by the presence of MUC16, the only known ligand of mesothelin, nor by the therapeutic antibody amatuximab. In vivo experiments showed that both ATTO 647N and [68Ga]Ga-NODAGA-S1 rapidly and specifically accumulated in mesothelin positive tumours compared to mesothelin negative tumours or irrelevant Nb with a high tumour/background ratio. The ex vivo biodistribution profile analysis also confirmed a significantly higher uptake of Nb S1 in MSLN-positive tumours than in MSLNlow tumours. Conclusion We demonstrated for the first time the use of an anti-MSLN nanobody as PET radiotracer for same day imaging of MSLN+ tumours, targeting an epitope compatible with the monitoring of amatuximab-based therapies and current SS1-derived-drug conjugates.